Pengaruh Kepemilikan Institusional, Profitabilitas, Corporate Social Responsibility (CSR) Terhadap Nilai Perusahaan Pada Perusahaan BUMN Yang Terdaftar Di BEI Tahun 2019-2022 - Fitrianingsih; Widyarti, Maria Theresia Heni; Budiyono, Iwan (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2024)
This research expects to choose the result of institutional ownership, profitability, CSR in direction of firm value. This reseacrh employs a quantitative procedure with discretionary data sources as yearly reports and company reasonability reports. The general population in this research were guaranteed by the state associations recorded on the IDX in 2019-2022. The data combination strategy employed with purposive testing, with the objective that an illustration of 9 (nine) associations was gotten. The data was dealt with using SPSS variation 27.00. The results of the audit showed that institutional belonging impacted firm value. Meanwhile, efficiency an CSR didn't impat tfirm value. Institutional ownership, profitability, CSR simultaneously impact firm value. This examination is supposed to be a reference for organizations to increment organization esteem and a reference for likely financial backers in putting resources into shares.